2006
DOI: 10.1038/ncpcardio0655
|View full text |Cite
|
Sign up to set email alerts
|

Principles for national and regional guidelines on cardiovascular disease prevention

Abstract: Cardiovascular disease (CVD) is the leading cause of global mortality resulting in nearly 17.5 million deaths worldwide in 2005. Whereas the causes of this epidemic involve the same risk factors, the approaches to its control and prevention can differ in each geographic region because of cultural, social, medical and economic circumstances. In recognition of the need for effective implementation of guidelines to curb the growing worldwide mortality from CVD, the World Heart Federation (WHF) has set forth princ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
94
0
6

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(100 citation statements)
references
References 6 publications
0
94
0
6
Order By: Relevance
“…In addition, serum TG is also considered an important risk factor for atherosclerosis [43,44]. Elevated levels of serum TG and LDL, accompanied by reduced HDL levels, are often associated with an increased risk of coronary heart disease [45]. In particular, many studies have found LDL to be the most dangerous among the serum lipids, and the oxidation of LDL leads to its increased penetration of arterial walls [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, serum TG is also considered an important risk factor for atherosclerosis [43,44]. Elevated levels of serum TG and LDL, accompanied by reduced HDL levels, are often associated with an increased risk of coronary heart disease [45]. In particular, many studies have found LDL to be the most dangerous among the serum lipids, and the oxidation of LDL leads to its increased penetration of arterial walls [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…Coronary heart disease (CHD) is a leading cause of global mortality, accounting for almost 17 million deaths every year (Smith et al 2004). Nearly 80 % of this mortality and disease burden occurs in the industrialized countries; the data for Spain refl ect this picture (Instituto Nacional de Estadistica, 2001).…”
mentioning
confidence: 99%
“…11 The World Heart Federation has outlined principles for national and regional guidelines for CVD prevention that outline essential concepts to assist with the development of guideline-related programs for CVD prevention. 12 As the Institute of Medicine pointed out in its recent report, prevention and better control of CVD worldwide, particularly in low-and middle-income countries, requires coordinated global and local actions to provide sustained efforts, strong leadership, stakeholder collaborations, and substantial investment of financial, technical, and human resources. 13 China now finds itself facing a major crisis with the predicted increase mortality and morbidity from CVD.…”
Section: Article See P 243mentioning
confidence: 99%